Determinants of Household’s’ Food and Nutrition Security in Indonesia - Lestari, Esta (Pusat Penelitian Ekonomi-LIPI, 2018)
Indonesia has experienced a significant improvement in its status of food security, yet it is not followed by improvement in nutritional security. Number of regions with food insecurity decreased significantly however problems of malnutrition among children such as stunting rate peaked for above 37% and obesity rate for just below 20%; known as double-burden malnutrition. This study aimed to examine factors affecting the nutritional security for households in Indonesia by incorporating food and non-food data. Cross sectional regression model is employed from SUSENAS 2013 in which households’ food security is proxy by calorie intakes as a function of households’ expenditures, mother’s age, mother’s education, dummy of closet types, number of member in households, and dummy of access to clean water. The results showed that several variables are positively affects households’ dietary intake namely expenditure, mother’s age, and mother’s education. Moreover, the other variables are negatively and significantly affect food consumptions namely type of closet, number of family member and type of clean water. The result implies that the government need to take significant strategies and program to address problems of nutrition by conducting two strategies, 1) changes in households food consumption pattern through shifted mindset and perception of parents’ from knowledge (especially mothers’) in healthy food consumption, 2) improving infrastructure and access for clean water, sanitation, and social security to broaden access of poor for better health status.